Dancing Solo - Jake Maddox (Stone Arch Books, 2014)
Sarah knows she's the best dancer in her class, and she can't wait to show off at the upcoming recital. But when a new move proves too tough to master, Sarah is forced to do something she's never had to do before - ask for help.
Keywords: Sport Stories -- Sport Stories